Suppression of X-ray-induced radiation damage to biomolecules in aqueous environments by immediate intermolecular decay of inner-shell vacancies - Hans, Andreas; Schmidt, Philipp; Küstner-Wetekam, Catmarna; Trinter, Florian; Deinert, Sascha; Bloß, Dana; Viehmann, Johannes H.; Schaf, Rebecca; Gerstel, Miriam; Saak, Clara M.; Buck, Jens; Klumpp, Stephan; et al. (The journal of physical chemistry letters, 2021)
The predominant reason for the damaging power of high-energy radiation is multiple ionization of a molecule, either direct or via the decay of highly excited intermediates, as, e.g., in the case of X-ray irradiation. Consequently, the molecule is irreparably damaged by the subsequent fragmentation in a Coulomb explosion. In an aqueous environment, however, it has been observed that irradiated molecules may be saved from fragmentation presumably by charge and energy dissipation mechanisms. Here, we show that the protective eﬀect of the environment sets in even earlier than hitherto expected, namely immediately after single inner-shell ionization. By combining coincidence measurements of the fragmentation of X-ray-irradiated microsolvated pyrimidine molecules with theoretical calculations, we identify direct intermolecular electronic decay as the protective mechanism, outrunning the usually dominant Auger decay. Our results demonstrate that such processes play a key role in charge delocalization and have to be considered in investigations and models on high-energy radiation damage in realistic environments.